Eksposisi Terhadap Ketujuh Cawan Penghakiman Allah Atas Babel Dalam Wahyu 16 - Simanungkalit, Hulman; Tambunan, Parsaoran; Aroean, Anita Suryani (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Â The Book of Revelation is a section that remains interesting to be studied in depth. When the writer conducts the study of this passage there is a tremendous admiration for God who is perfect in His design and perfect in His omniscience. The author is interested in highlighting this because of the challenges in conducting a study of texts that have difficulties in interpreting. A large number of symbols in this section and the many other things that need to be considered are difficulties in providing enrichment of New Testament study materials. The exposition of the selected text also considers that there is a dynamic in the interpretation of the Apocalyptic book. Throughout history, many theologians have undertaken this study, and continue to make their contributions. Likewise, the author feels the need to contribute as a form of an active role in enriching the scientific treasures of theology students. The seven bowls in question are dug up with exegesis steps so that the meaning that is most follows the depth of meaning intended by the author of the book is obtained.Keywords: the cup; God's wrath; revelation; exposition.